The roles of social media and traditional news media in promoting government responsiveness in social incidents - Yuan, Lihong; Razi, Siti Aishah binti Hj Mohammad; Mahamed, Mastura; Kasimon, Diyana Nawar Binti (Redfame Publishing, 2024)
Social media is considered to play an important role in promoting government responsiveness. However, it is impossible for the government to respond to all issues in the actual situation. Especially when encountering controversial social incidents, the local government usually evades responsibility due to damage to reputation or interests. This paper argues that when a controversial social incident occurs in China, the traditional news media will work with social media to encourage the local government to respond. Three cases are selected according to the hot discussion index of Sina Weibo, China's largest social media platform for multiple-case studies. 21 participants were interviewed to explore the function of social media and traditional news media during the process of government responsiveness. The results showed that traditional news media played the role of professionalism, supervision, and broker to develop social incidents. And social media took the information aggregation part in most situations. Social media and traditional news media work together to promote the local government to make government responsiveness active.